2015
DOI: 10.1080/15476286.2015.1050576
|View full text |Cite
|
Sign up to set email alerts
|

Identification of determinants for tRNA substrate recognition byEscherichia coliC/U34 2′-O-methyltransferase

Abstract: (2015) Identification of determinants for tRNA substrate recognition by Escherichiacoli C/ U34 2′-O-methyltransferase, RNA Biology, 12:8, 900-911,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…Thus, the 5-carboxymethylaminomethyl group in cmnm 5 U34 is not involved in the recognition of tRNA by TrmL. Furthermore, the methylation of stem-loop RNA by TrmL [70] is consistent with the aforementioned proposed docking model of TrmL and tRNA [54]. …”
Section: Transfer Rna Recognition Mechanismmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, the 5-carboxymethylaminomethyl group in cmnm 5 U34 is not involved in the recognition of tRNA by TrmL. Furthermore, the methylation of stem-loop RNA by TrmL [70] is consistent with the aforementioned proposed docking model of TrmL and tRNA [54]. …”
Section: Transfer Rna Recognition Mechanismmentioning
confidence: 53%
“…This model suggested a possibility of direct interaction between TrmL and ms 2 i 6 A37 in tRNA [54]. In 2015, it was reported that chemically synthesized stem-loop RNA containing Ψ32, i 6 A37 and Ψ39 was methylated by TrmL: the ribose methylation occurred at unmodified U34 [70]. Thus, the 5-carboxymethylaminomethyl group in cmnm 5 U34 is not involved in the recognition of tRNA by TrmL.…”
Section: Transfer Rna Recognition Mechanismmentioning
confidence: 99%
“…Two SPOUT enzymes, TrmL (tRNA Um 34 /Cm 34 ) and RlmH (rRNA), are considered “minimalist” proteins where substrate binding is limited solely to the SPOUT domain and, in the case of TrmL, no other RNA-binding protein assists in binding [25,4951]. TrmL acts as a homodimer to catalyze 2′-O-methylation at position 34 on two isoacceptors of tRNA Leu (anticodons: CAA and UAA), and like many RNA-binding enzymes, it uses positively charged residues for substrate recognition [50,51]. Interestingly, only three other SPOUT tRNA methyltransferases are found in bacteria (TrmH, TrmD, and TrmJ); all methylate many more different substrates than TrmL [50].…”
Section: The Diversity Of Rna Methylations Methyltransferases and Tmentioning
confidence: 99%
“…TrmL acts as a homodimer to catalyze 2′-O-methylation at position 34 on two isoacceptors of tRNA Leu (anticodons: CAA and UAA), and like many RNA-binding enzymes, it uses positively charged residues for substrate recognition [50,51]. Interestingly, only three other SPOUT tRNA methyltransferases are found in bacteria (TrmH, TrmD, and TrmJ); all methylate many more different substrates than TrmL [50]. Presumably, these enzymes acquired nucleic acid-binding domains as N- and C-terminal extensions that support recognition of multiple substrates, whereas the minimal SPOUT enzyme TrmL binds fewer substrates, making these extensions unnecessary.…”
Section: The Diversity Of Rna Methylations Methyltransferases and Tmentioning
confidence: 99%
“…Some of the site-specific enzymes act on essentially all tRNAs containing an appropriate target residue, like TrmA from Escherichia coli , which methylates uridine at position 54 in practically all tRNAs that have this residue [9]. Other enzymes act only on a subset of available substrates that conform to their requirements of sequence, structure and/or presence of other modifications – examples include TrmL [10] and TruA [11] from E. coli .…”
Section: Introductionmentioning
confidence: 99%